2009
DOI: 10.1007/s10719-009-9238-9
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the sialylation patterns of membrane stress proteins in chemical carcinogen-induced tumors developed in BALB/c and IL-1α deficient mice

Abstract: We evaluated the patterns of sialylation on fibrosarcoma cell lines arising following 3-methylcholanthrene treatments of wild-type and IL-1alpha-deficient mice; the former induced progressive tumors, whereas the latter cell lines induced regressing tumors or failed to develop into tumors in mice due to immune rejection. In regressing tumors, terminating alpha2-6-Neu5Ac residues were present at lower levels than in progressively growing tumors. In both tumor cells, the amount of alpha2-6-Neu5Ac residues was hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 39 publications
(45 reference statements)
1
14
0
Order By: Relevance
“…mice, we detected lower expression of a2-6 sialyltransferase, compared with MCA-induced lines derived from WT mice, which corroborates the results of Avidan et al (19). Our data suggest that sialylation of the tumor cell surface or sialylation of specific moieties determines the differential ability to stimulate different immune responses.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…mice, we detected lower expression of a2-6 sialyltransferase, compared with MCA-induced lines derived from WT mice, which corroborates the results of Avidan et al (19). Our data suggest that sialylation of the tumor cell surface or sialylation of specific moieties determines the differential ability to stimulate different immune responses.…”
Section: Discussionsupporting
confidence: 91%
“…The renewal of sialic acid levels to the original status was examined in sialidase-treated WT and IL-1a 2/2 fibrosarcoma cell lines. According to our previous study, MCAinduced fibrosarcoma cell lines derived from IL-1a 2/2 mice express lower amounts of a2-6 sialyltransferase (ST6GalI) compared with fibrosarcoma cells derived from naive BALB/c mice (19). Therefore, the recovery of sialic acids on IL-1a 2/2 tumor cells was also 50% lower than sialic acid recovery on fibrosarcoma cell lines derived from BALB/c mice at the same time (Supplemental Fig.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…The gels were run in a MiniProtean3 device (Bio-Rad) for 75 min at 140–170 mV, at a current lower than 350 mA [18]. The IgG molecules were visualized with Coomassie blue stain and the relevant bands were excised, cut into small pieces and dried using vacuum centrifugation.…”
Section: Methodsmentioning
confidence: 99%
“…Another line of evidence indicating the importance of sialylation in tumor immunology is a recent study in the methylcholanthrene induced fibrosarcoma model (199,200). It was observed that methylcholanthrene induced fibrosarcomas grown in immunecompetent mice expressed high levels of sialic acid on their cell surface.…”
Section: Sialylated N-linked or O-linked Glycans-sialylation Of Glycomentioning
confidence: 99%